2022
DOI: 10.1177/00957984211070216
|View full text |Cite
|
Sign up to set email alerts
|

Lawyering While Black: Perceived Stress as a Mediator of Impostor Feelings, Race-Related Stress and Mental Health Among Black Attorneys

Abstract: Attorneys suffer from high rates of stress and mental health problems, and Black attorneys, who make up only five percent of all attorneys in the United States, are especially vulnerable due to underrepresentation and experiences of bias. The present study examined perceived stress as a mediator of the impostor phenomenon, race-related stress, and mental health among a sample of 142 Black attorneys (114 women, 25 men). Gender, age, impostor phenomenon, race-related stress, and perceived stress accounted for 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
2
2
0
Order By: Relevance
“…Between 14 and 19 percent of the respondents were categorized as Competent Ally Impostors. Consistent with the previous literature on impostorism and mental health, we found that Competent Ally Impostors had significantly stronger depressive scores (Murphy et al, 2009;Kumar & Jagacinski, 2006) and anxiety scores (Cokley et al, 2022) than their non-impostor counterparts.…”
Section: Discussionsupporting
confidence: 91%
“…Between 14 and 19 percent of the respondents were categorized as Competent Ally Impostors. Consistent with the previous literature on impostorism and mental health, we found that Competent Ally Impostors had significantly stronger depressive scores (Murphy et al, 2009;Kumar & Jagacinski, 2006) and anxiety scores (Cokley et al, 2022) than their non-impostor counterparts.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with the biopsychosocial model of racism and previous research that found positive associations between individual racism and depression and anxiety outcomes broadly (e.g., Assari et al, 2017;Greer & Cavalhieri, 2019;Greer et al, 2009;Greer & Spalding, 2017;Ikram et al, 2016;Yip et al, 2008). Our findings are also aligned with the few studies that have examined associations of cultural and institutional race-related stress with mood symptoms among Black or African American adults, which also documented positive associations (Cokley et al, 2022;D. B. Lee et al, 2015;MacNear & Hunter, 2023;Obenauf et al, 2023).…”
Section: Discussionsupporting
confidence: 91%
“…Given the lack of a buffering effect found for depressive symptoms, future research efforts should also aim to understand additional race- and culture-related factors that may mitigate the deleterious impact of race-related stress on depressive symptoms among ERMs, continuing to disaggregate by type of mood symptom. This work is particularly needed among Latinx, Asian, multiracial, and American Indian/Alaskan Native groups, as most of what was previously known about the impact and moderators of cultural and institutional race-related stress is based on samples of Black/African American people (e.g., Cokley et al, 2022; D. B. Lee et al, 2015; MacNear & Hunter, 2023; Obenauf et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Research on the mental health of lawyers generally falls short of including measures of suicidality, but offers some leads on well-being that may be relevant to predicting suicidality (Benjamin et al, 1990;Cokley et al, 2022;Eaton et al, 1990;Hagan & Kay, 2007;Kay & Wallace, 2009;Koenig, 2019;Koltai et al, 2018;Krill et al, 2016;Nelson et al, 2019;Nielson & Minda, 2021;Organ et al, 2016;Scott, 2018;Sendroiu et al, 2021). The results are mixed, but tend to suggest evidence of lower than average mental well-being among attorneys.…”
Section: Lawyer Mental Healthmentioning
confidence: 99%